Paracoccidioidomycosis due to Paracoccidioides lutzii complicated with adrenal injury and pulmonary arterial hypertension - Gaspar, Gilberto Gambero; Cocio, Tiago Alexandre; Guioti-Puga, Fernanda; Nascimento, Erika; Fabro, Alexandre Todorovic; von Zeska Kress, Marcia Regina; Bagagli, Eduardo [UNESP]; Martinez, Roberto (Inst Medicina Tropical Sao Paulo, 2020)
Paracoccidioidomycosis caused by Paracoccidioides lutzii is endemic in the Midwest of Brazil and its clinical spectrum is still little known due to the recent identification of this fungal species. A patient resident in Southeast Brazil, but who had lived for many years in the Midwest region, presented with skin injuries, chronic cough and bilateral adrenal involvement. Paracoccidioides spp. was isolated in culture from a skin lesion biopsy. This isolate was later identified as P. lutzii using gene sequencing. A favorable initial response to treatment with itraconazole was observed, but a few weeks later, the patient developed respiratory failure and worsening of lung lesions. Evaluation by computed tomography and echocardiography were suggestive of pulmonary arterial hypertension, and a bronchoscopic biopsy showed peribronchial remodeling. The patient completed the antifungal treatment but maintained the respiratory dysfunction. The reported case shows that P. lutzii can be isolated from patients in a geographic area far from the place of infection acquisition and that, as P. brasiliensis, it can cause adrenal injury and cardio-respiratory complications as a consequence of excessive necrosis and fibrosis.
Keywords: Paracoccidioidomycosis; Paracoccidioides lutzii; Pulmonary arterial hypertension